Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Sosial Emosional Anak Yang Menggunakan Gadget Pada Anak Usia Dini - Azwi, Arfina Indah; Yenni, Yenni; Vianis, Okta (REAL in Nursing Journal, 2022)
Background: The use of gadgets in the age group less than 5 years in Indonesia is quite high. It is around 80%. This number tends to increase during the pandemic that give the changes in the order of life and education. The condition requires good attention and supervision from parents so that the use of gadgets can be controlled and does not affect children's development. This research aims to determine The Correlation between Parenting Patterns Toward Social Emotional Development of Gadget Children Users in Early Childhood at Al-Azhar Kindergarten Bukittinggi. Methods: This type of this research was descriptive analytic with a cross sectional study approach. It has been carried out on September - November 2020 with a population of all parents of early childhood in Al-Azhar Kindergarten,  they were 60 respondents. The data were collected through questionnaires and it was analyzed by univariate analysis and bivariate analysis. Results: The results showed that 81.7% of respondents were democratic gadget parenting style and 63.3% of respondents had good social emotional development. The results of statistical analysis showed that there was a relationship between parenting patterns and social emotional development of early childhood who used the gadgets with p=0.014. Conclusiona: It is concluded that parenting style is significantly related to social emotional development of gadget early childhood users. Therefore, it is expected for parents to do good parenting (in this case democratic) in terms of the use of gadgets in early childhood.